2006
DOI: 10.1021/op050227k
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry, a Pharmaceutical Perspective

Abstract: As the Green Chemistry 1,2 movement has gained momentum, definitions of Green Chemistry have been dominated predominantly by academic viewpoints. Green Chemistry concepts, however, apply to an incredible diversity of scientific endeavor, which has invariably led to differences between and amongst both academia and industry regarding what constitutes Green Chemistry. Speaking primarily of the pharmaceutical industry and considering the advances achieved toward promoting Green Chemistry globally, 3 it is surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
89
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(93 citation statements)
references
References 16 publications
0
89
0
4
Order By: Relevance
“…Furthermore and importantly,w ee nvisagedt hat the developed methodw ould be applicable in aw ide variety of more environmentally acceptable solvents. [12] We initiatedo ur studies by examining the nature of our developed catalyst speciesa nd evaluatedarange of NHC/phosphine complexes 3 in the hydrogenation of (E)-4-phenylbut-3-en-2-one 1a (Table 1). For comparison, we examined the reaction with Crabtree's catalyst 3a and found that only 31 %c onversionw as achieveda tt he low applied catalyst loading (entry 1).…”
mentioning
confidence: 99%
“…Furthermore and importantly,w ee nvisagedt hat the developed methodw ould be applicable in aw ide variety of more environmentally acceptable solvents. [12] We initiatedo ur studies by examining the nature of our developed catalyst speciesa nd evaluatedarange of NHC/phosphine complexes 3 in the hydrogenation of (E)-4-phenylbut-3-en-2-one 1a (Table 1). For comparison, we examined the reaction with Crabtree's catalyst 3a and found that only 31 %c onversionw as achieveda tt he low applied catalyst loading (entry 1).…”
mentioning
confidence: 99%
“…But life saving drugs must be enabled. Some of green chemistry principles are used to meet goals to reduce environmental impact and higher efficiency through absolute best performance [10]. Green Chemistry principles carry environmental advantages to pharmaceutical companiesVarious environmental benefits are seen because of certain parameters.…”
Section: Implementation Of Green Initiatives In Pharmaceutical Imentioning
confidence: 99%
“…Further, process efficiency is also improved. The above mentioned points reduce environmental burden [10].…”
Section: Implementation Of Green Initiatives In Pharmaceutical Imentioning
confidence: 99%
“…Recently, the (bio)pharmaceutical industry introduced safety and health regulations to protect the environmental criteria for their products [1]. The using of toxic organic solvents for the synthesis and analysis of drugs is critical on a number of levels [2].…”
Section: Introductionmentioning
confidence: 99%